Assessment of mercury and natural radioactivity in sediments from a small-scale gold mining legacy tailings pond in Camarines Norte, Philippines - De Juan, Airah Sophia J.; Villanueva, Margarette Denise Leine; Arpa, Maria Carmencita B.; Samaniego, Jessie O.; Peregrino, Fern Rose A. (Brawijaya University, 2026)
Jose Panganiban, Camarines Norte, is notable for small-scale gold mining, which produces waste stored in tailings storage facilities such as tailings ponds. These operations potentially pose environmental risks to nearby ecosystems and local communities due to hazardous substances, including mercury (Hg) used in ore processing, and elevated radionuclide concentrations from land disturbance. This study assessed the presence of the abovementioned pollutants in a legacy tailings pond to evaluate human and environmental risks. Sampling points were established around the pond for in-situ gamma-ray spectrometry measurements of radionuclides and for laboratory analysis of mercury. Assessment of radiological risk parameters showed that computed values were well below established global averages. Radiological assessments used NORMALYSA simulation, and results indicated that the absorbed dose rate in the study area remains below the public safety limit of 1 mSv/year. In contrast, mercury analysis revealed that certain sampling points exceeded the global background for soils, indicating localized contamination. Mercury speciation analysis reveals that Hg(I) was the predominant mercury species identified in soil samples. The geoaccumulation index assessment indicated that some sites are strongly to extremely contaminated with mercury, while locations farther from the tailings pond exhibited minimal risk of mercury contamination. Although radiometric analysis did not detect anomalous radionuclide elevation attributable to mine waste, localized mercury contamination remains a significant environmental concern.